Identifikasi Keselamatan dan Kesehatan Kerja dengan Metode Job Safety Analysis (JSA) di Industri Bengkel Farisna, Semarang - Ismi Elya Wirdati; Annisa Nur Utami; Lutfi Muzaqi; Izzatul Alifah Sifai (Jurnal Kesehatan Amanah, 2024)
Hazard identification and risk assessment in the Farisna workshop are classified based on the work performed. The use of machinery, equipment, supporting materials, workshop environment, and mechanical work procedures can be a source of potential hazards for workers in the workshop, therefore it is necessary to evaluate health in the Farisna workshop to prevent the risk of harm. This study aims to determine the planning and evaluation of occupational health in the engineering sector in the Farisna workshop. This research method is descriptive qualitative. Using total sampling technique. Data collection by observation with research instruments using JSA or Job Safety forms. The results of this study indicate that of the 7 work activities in the workshop there are 5 activities with medium or medium risk, and there are 2 high risk or high. Medium risks such as being crushed and crushed by heat stress montors, heat disorders, slipping and skin irritation, skin blisters, scratches and punctures, back pain. While the high risk of work activities in the workshop is exposed to explosions, burns, skin irritation, and respiratory problems. Prevention to avoid the risk of work in the workshop should be when working using PPE, doing work carefully, and putting tools in place, and providing fire extinguishers to prevent accidents.